Excess Molar Volume Parameters of Amido-aromatic Ketone Binary Solvent Systems at 308.15 K - Savitha Jyostna, T.; Satyanarayana, N. (Asian Journal of Chemistry, 2016)
Densities have been measured for the systems, N,N-dimethyl acetamide + phenones (acetophenone, propiophenone, p-methyl acetophenone and p-chloro acetophenone) at 308.15 K. These values have been converted to excess molar volumes. The excess molar volumes are negative for all the mixtures over the entire composition range. The molecular interactions existing between the components are discussed.